2021
DOI: 10.21203/rs.3.rs-226857/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccine-induced immunity provides more robust heterotypic immunity than natural infection to emerging SARS-CoV-2 variants of concern.

Abstract: Both natural infection with SARS-CoV-2 and immunization with a number of vaccines induce protective immunity. However, the ability of such immune responses to recognize and therefore protect against emerging variants is a matter of increasing importance. Such variants of concern (VOC) include isolates of lineage B1.1.7, first identified in the UK, and B1.351, first identified in South Africa. Our data confirm that VOC, particularly those with substitutions at residues 484 and 417 escape neutralization by antib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 22 publications
4
57
0
Order By: Relevance
“…Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021). However, since the correlate of protection is not yet established for SARS-CoV-2, the significance of this drop is still not clear.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021). However, since the correlate of protection is not yet established for SARS-CoV-2, the significance of this drop is still not clear.…”
Section: Discussionsupporting
confidence: 84%
“…Against authentic SARS-CoV-2, convalescent and BNT162b2 vaccine serum titres were equivalent against a mouse-adapted strain with N501Y and the parental strain (Rathnasinghe et al, 2021), whereas a full B.1.1.7 isolate showed a two-fold reduction in neutralisation by BNT162b2 vaccine sera (Diamond et al, 2021). Others have reported a 2-fold reduction in neutralisation of authentic B.1.1.7 virus by both convalescent and BNT162b2 vaccine sera with some convalescent sera which weakly neutralise the WT virus falling below the threshold of detection against B.1.1.7 (Skelly et al, 2021). Taken together, the evidence to date shows that the B.1.1.7 variant is equivalently or slightly less well neutralised by polyclonal sera and does not yet present a substantial risk of escape from pre-existing or vaccine-induced antibody immunity.…”
Section: Introductionmentioning
confidence: 98%
“…While escape from neutralisation in vitro is an important line of evidence as to whether emerging strains will escape pre-existing immunity or not, other factors such as non-neutralising antigen-specific antibodies, T cells and innate lymphocytes clearly have the potential to contribute protection in vivo [21][22][23][24] . Indeed, recent work has shown that T cell epitopes that dominate human SARS-CoV-2 responses are not subject to major substitution in the three variants of concern 5 . Further, it is known that previous infection with influenza virus results in reduced disease against subsequent infection with heterosubtypic strains, in both human and animals, demonstrating the power of cellmediated immunity and non-neutralising antibodies in protection [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…21 Reinfection rates following natural infection have not been shown to be higher in studies using SGTF as a proxy for B.1.1.7, 20,22 even though variably decreased sensitivity to neutralisation by monoclonal antibodies, convalescent plasma and sera from vaccinated individuals has been observed in vitro for B.1.1.7. [23][24][25][26][27][28][29][30][31][32][33][34] The Oxford-AstraZeneca trial showed good vaccine efficacy against sequencingconfirmed symptomatic B.1.1.7, despite evidence of decreased neutralising titres, but decreased efficacy for asymptomatic/unknown symptom infections. 35 Pfizer-BioNTech vaccine effectiveness in HCWs appears preserved despite increasing B.1.1.7 incidence in the UK; however these studies have not specifically investigated cases of SGTF or sequencing-confirmed B.1.1.7.…”
Section: Introductionmentioning
confidence: 99%